Synthesis, Characterization and Antimicrobial Activity of Triazamacrocyclic Based Polymeric Ligand and its Polymer-Metal Complexes - M. Alshehri, Saad; Al-Farraj, Eida; Alhokbany, Norah; Ahamad, Tansir (Asian Journal of Chemistry, 2015)
A triazamacrocyclic-based polymeric ligand (poly-H3L) was synthesized via polycondensation of 1,4,7-triazacyclonone-1,4,7-tripropionic acid (NOTPA) and ethylenediamine and polymer-metal complexes were prepared with Cu(II), Zn(II), In(III) and Ga(III) ions. All of the synthesized polymers were characterized by elemental, spectral and thermal analyses. The elemental and spectral data revealed that the poly-HLM(II) are five-coordinate complexes in which the metals are coordinated to three nitrogen atoms in the macrocycle and are coordinate covalently bound to two amide groups. However, the poly-LM(III) are six-coordinate complexes. The thermal kinetics, such as the activation energy and the thermodynamic parameters of the synthesized polymers were evaluated during pyrolysis using the Coats-Redfern equation. In addition, the antimicrobial activity of the synthesized polymers was evaluated against several microorganisms using agar-well diffusion methods. Among all of the polymer-metal complexes, the antimicrobial activity of the Cu(II)-chelated polymer exhibited the largest zone of inhibition.